THE IMAGE OF BUKHARA IN ANTHONY JENKINSON'S "TRAVELLING OF MISTER ANTHONY JENKINSON FROM MOSCOW, RUSSIA TO BUKHARA IN 1558, WRITTEN BY HIMSELF FOR LONDON MERCHANTS OF MOSCOW COMPANY" (Scientific journal of the Fergana State University, 2023)
In this article the establishment of trade relations via England in the second half of 16th century between Russia and Bukhara is examined.  Anthony Jenkinson, who was a representative of English Moscow company, which held a monopoly on trade with Russia, had a mission there and he depicted the image of Bukhara in his notes.